2023
DOI: 10.1111/zsc.12593
|View full text |Cite
|
Sign up to set email alerts
|

The role of systematics for understanding ecosystem functions: Proceedings of the Zoologica Scripta Symposium, Oslo, Norway, 25 August 2022

Abstract: On 25 August 2022, the Zoologica Scripta -An International Journal of Systematic Zoology and the Norwegian Academy of Sciences and Letters arranged a symposium entitled 'The role of systematics for understanding ecosystem functions' in the Academy's premises in Oslo, Norway. The symposium aimed at offering a forum for exploring and discussing trends and future developments in the field of systematics. Eleven international experts contributed expertise on various issues related to global challenges, such as bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 215 publications
(232 reference statements)
0
6
0
Order By: Relevance
“…Though time itself is a precious resource in our modern world, maintaining and improving these public databases is a task achievable without personal access to expensive computational equipment, thanks to publicly accessible servers. The large-scale revisions to GenBank that are implied by Pappalardo & Osborn in Bachmann et al (2023) and this study may initially seem daunting, but with simple protocols and a widespread devotion of just a small amount of time, the mountain of data could become far more manageable, and result in not just a "fixed" database, but one fundamentally better than before.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Though time itself is a precious resource in our modern world, maintaining and improving these public databases is a task achievable without personal access to expensive computational equipment, thanks to publicly accessible servers. The large-scale revisions to GenBank that are implied by Pappalardo & Osborn in Bachmann et al (2023) and this study may initially seem daunting, but with simple protocols and a widespread devotion of just a small amount of time, the mountain of data could become far more manageable, and result in not just a "fixed" database, but one fundamentally better than before.…”
Section: Discussionmentioning
confidence: 81%
“…A primary concern explicated by this analysis – and by Pappalardo & Osborn in Bachmann et al (2023) – is the number of misattributed sequences in GenBank: sequences identified as belonging to, in some cases, a different phyla owing to the nature of eDNA studies. In our initial BLAST analysis, we rejected 283 of the 631 test sequences (44.8%) identified as Tardigrada 18S (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to explore future trends in biosystematics, the Zoologica Scripta and the Norwegian Academy of Sciences and Letters (DNVA), organized in August 2022 a symposium entitled 'The role of systematics for understanding ecosystem functions'. We particularly appreciated that many of the speakers at the symposium contributed to a special proceedings paper (see contributions by Bachmann et al (2023) and Glaubrecht (2023) this issue) summarizing the major issues discussed at the meeting.…”
Section: E D I T O R I a Lmentioning
confidence: 99%